Thai coup : continued political divide and uncertainty - Tan, Seng Chye (2014)
The Thai Military’s takeover of the government on 22 May afternoon following the declaration of Martial Law on 2- May 2014, is seen a movie to support the royalist elites to oust the Puea thai government. Political divide among the Thai people has deepened and the political uncertainly will continue.